2013
DOI: 10.1371/journal.pone.0080637
|View full text |Cite
|
Sign up to set email alerts
|

The α and Δ Isoforms of CREB1 Are Required to Maintain Normal Pulmonary Vascular Resistance

Abstract: Chronic hypoxia causes pulmonary hypertension associated with structural alterations in pulmonary vessels and sustained vasoconstriction. The transcriptional mechanisms responsible for these distinctive changes are unclear. We have previously reported that CREB1 is activated in the lung in response to alveolar hypoxia but not in other organs. To directly investigate the role of α and Δ isoforms of CREB1 in the regulation of pulmonary vascular resistance we examined the responses of mice in which these isoforms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Previous findings by catheterization of the left ventricle showed that Crem −/− mice exhibit a lower left-ventricular blood pressure than Crem +/+ animals [ 27 ], which could be associated with alterations in the contractility of the vascular system. Moreover, a loss of the Creb isoforms α and Δ was linked to a higher pulmonary vascular resistance [ 23 ]. Our analysis revealed that neither the PE- or prostaglandin-mediated vasoconstriction nor the β-adrenergic, muscarinic, or NO-dependent vasorelaxation was different concerning the maximal effects or the EC 50 /IC 50 in Crem −/− mice versus Crem +/+ mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous findings by catheterization of the left ventricle showed that Crem −/− mice exhibit a lower left-ventricular blood pressure than Crem +/+ animals [ 27 ], which could be associated with alterations in the contractility of the vascular system. Moreover, a loss of the Creb isoforms α and Δ was linked to a higher pulmonary vascular resistance [ 23 ]. Our analysis revealed that neither the PE- or prostaglandin-mediated vasoconstriction nor the β-adrenergic, muscarinic, or NO-dependent vasorelaxation was different concerning the maximal effects or the EC 50 /IC 50 in Crem −/− mice versus Crem +/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclic AMP promotes quiescence and maintenance in vascular smooth muscle cells (VSMCs) and the β-adrenoceptor, and cAMP-dependent activation of PKA is important to sustain their contractile function under normal conditions [ 35 ]. Creb is an important downstream target of PKA, and changes in Creb phosphorylation or function are correlated with the regulation of cell proliferation [ 18 , 41 ], apoptosis [ 42 ], migration [ 15 , 29 ], VSMC hypertrophy [ 8 ], or vascular resistance [ 23 ]. Elevated cAMP levels inhibit platelet-derived growth factor (Pdgf)-stimulated VSMC growth by PKA/Creb-dependent induction of transformation-related protein 53 (p53) and cyclin-dependent kinase inhibitor 1A (p21) and by inhibition of mitogen-activated protein kinase (MAPK) signaling [ 2 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hearts were separated from the lungs, fixed by immersion in paraformaldehyde (4% w/v in normal saline) and used to determine the ratio of the right ventricle to the left ventricle plus septum (RV/LV + S) as previously described. 29 Briefly, the atria were removed at the level of the atrioventricular junction in the plane of the mitral and tricuspid annuli (i.e. at the level of the openings of the tricuspid and mitral valves where the valve leaflets attach).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, there are reports showing the downregulation of pCREB in PAH PASMCs and the protective role of CREB from proliferation and remolding by regulating phosphatase and tension homolog (PTEN), a tumor suppressor gene, and mitochondrial calcium uniporter (MCU), a mitochondrial calcium uptake protein that can decrease [Ca 2+ ] i [36,37]. These contradictory results may be due to the presence of three types of isoforms of CREB, which may produce different effects [38].…”
Section: Crebmentioning
confidence: 99%